Aqua Fanners Perceptions on Extension Services - A Paired Comparison Approach - Vimala. D, Deboral; C., Sarada; M., Krishnan (Fishery Technology, 2025)
Owing to the weak Research-Extension -Farmers linkage system, most of the technologies do not reach the farmers when they are in need. In this study extension services were categorized into five broad heads namely training programmes, communication support, extension programmes, method demonstration and technical assistance. An attempt has been made to study the farmer' s perception towards these extension services and prioritise these services. The psychological scale developed in this study indicated that communication support ranked first with a scale value of 0.647 followed by technical assistance (0.470), training programmes (0.182), extension programmes (0.026) and demonstrations (0). The order of priority of extension requirements was thus analysed that indicated that the farmers preferred good communication support and technical assistance. The transfer of technology can be made effective to the client system when it is need based.